Optimal sales schemes against interdependent buyers - Masaki Aoyagi (Osaka University, Institute of Social and Economic Research (ISER), 2005)
This paper studies a monopoly pricing problem when the seller can also choose the timing of a trade with each buyer endowed with private information about the seller's good. A buyer's valuation of the good is the weighted sum of his and other buyers' private signals, and is affected by the publicly observable outcomes of preceding transactions. We show that it is optimal for the seller to employ a sequential sales scheme in which trading with the buyers takes place one by one. Furthermore, when the degree of interdependence differs across buyers, we analyze how the optimal sales scheme orders them, and how it may induce herding among them.
Keywords: C72; D82; 330; timing; monopoly pricing; information revelation; linkage principle; social learning; Monopol; Preismanagement; Asymmetrische Information; Theorie; Nichtkooperatives Spiel